2016
DOI: 10.1021/acssuschemeng.5b01387
|View full text |Cite
|
Sign up to set email alerts
|

Efficient H2 Production Using Ag2S-Coupled ZnO@ZnS Core–Shell Nanorods Decorated Metal Wire Mesh as an Immobilized Hierarchical Photocatalyst

Abstract: Ag 2 S-coupled ZnO@ZnS core−shell nanorods heterostructures were grown on stainless steel wire mesh substrates along the c-axis by sulfidation of aligned ZnO nanorod arrays as immobilized hierarchical photocatalysts (Ag 2 S-coupled ZnO@ZnS/metal wire mesh) for photocatalytic H 2 production. The effects of the sulfidation time and AgNO 3 precursor concentration on the morphology, crystalline properties, optical property, photocurrent response, and photocatalytic H 2 production activity of the photocatalysts und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(46 citation statements)
references
References 59 publications
(78 reference statements)
3
43
0
Order By: Relevance
“…Finally, the generated charge carrier is further accelerated by the disorder ZnS shell, and the hydrogen produced in the CB of ZnS. The presence of hole scavenger of Na 2 S and Na 2 SO 3 accelerates the photocatalytic hydrogen evolution because the photogenerated holes can be scavenged by SO 3 2− and S 2− , and simultaneously hydrogen ions ionized from H 2 O can be reduced by photogenerated electrons and H 2 can be produced stably upon 2D‐ZnS@ZnO photocatalyst . The reactions can be expressed as following (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the generated charge carrier is further accelerated by the disorder ZnS shell, and the hydrogen produced in the CB of ZnS. The presence of hole scavenger of Na 2 S and Na 2 SO 3 accelerates the photocatalytic hydrogen evolution because the photogenerated holes can be scavenged by SO 3 2− and S 2− , and simultaneously hydrogen ions ionized from H 2 O can be reduced by photogenerated electrons and H 2 can be produced stably upon 2D‐ZnS@ZnO photocatalyst . The reactions can be expressed as following (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it seems to be a Z‐scheme heterostructure rather than traditional II‐type heterostructure for ZnS@ZnO heterostructure in photocatalytic hydrogen production. Currently, one‐dimensional 1D‐ZnS@ZnO nanowires have been widely studied . At present, the 2D‐ZnS@ZnO through two step hydrothermal methods was rarely reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, sandwiched ZnO@Au@Cu2O nanorod films were synthesized on steel mesh substrates via a simple three-step approach and showed an efficient visible-light photocatalytic performance for the degradation of the MO solution [142]. Those non-doped ZnO hierarchical composites could also be used in the field of H2 generation [118,122,[143][144][145][146][147][148][149][150]. Barpuzary et al [143] prepared urchin-like CdS@ZnO hetero-arrays via a template-based method.…”
Section: Photocatalytic Applications Of Hierarchical Zno Nanostructurmentioning
confidence: 99%
“…The heterostructure of CdS/Au/ZnO showed improved photocatalytic hydrogen evolution rate with 60.8 mmol h −1 , which was 4.5-times higher than the CdS/ZnO heterostructure. Furthermore, Hsu et al [146] reported that a hierarchical Ag2S-coupled ZnO@ZnS core−shell nanorod-decorated metal wire mesh showed higher H2 production rates reaching 5870 and 168 μmol g -1 h −1 under UV and visible light irradiation than ZnO/metal mesh. Thus, the fabrication of hierarchical ZnO-based heterostructures is a promising strategy to enhance both photocatalytic degradation and H2 generation.…”
Section: Photocatalytic Applications Of Hierarchical Zno Nanostructurmentioning
confidence: 99%